74th UNGA Debate : Nationalism or Multilateralism? - Menon, Vijayalakshmi (2020)
The annual General Debate of the 74th session of the UN General Assembly session, which took place recently, reflected a world becoming more divided and polarised. While some questioned the benefits of globalisation others reaffirmed their belief in the necessity for multilateral action to tackle international problems.